The Role of Language Objectives: Strengthening Math and Science Teachers' Language Awareness with Emergent Bilinguals in Secondary Classrooms - Holly Hansen-Thomas; Juliet Langman; Tiffany Farias Sokoloski (Universidad de La Sabana, 2019)
El rol de los objetivos de lenguaje: fortaleciendo la conciencia lingüística de los maestros de matemáticas y ciencias con los bilingües emergentes en las clases secundarias O papel dos objetivos da linguagem: fortalecer a consciência linguística dos professores de matemática e ciências com os bilíngues emergentes nas aulas secundárias This study focuses on the linguistic foundation of sound pedagogic practices related to non-language content areas referring especially to language objectives; it employ Tharp and Gallimore's theory on learning: making teaching visible in order to develop the students' thinking. In the contexts of training both before and after service, a study was conducted on how secondary-science and math teachers contextualize their own teaching according to Emergent Bilinguals (EBs) by using interviews and focus group discussions. Findings reveal that teachers gradually develop an increased sense of importance of language objectives over time. The strengths and challenges highlighted through the study show the need for increased teacher training in the area of teacher language awareness (TLA). So far, the predominance of TLA in the classrooms has been on language, rather than content. Based on the current analysis of how content teachers define and employ language objectives in their teaching, this study proposes a few ways to provide math and science teachers with tools for incorporating language into everyday teaching practices. The present study further supports the call for attention on the needs of all content teachers who work with EBs on training in language awareness. To reference this article (APA) / Para citar este artículo (APA) / Para citar este artigo (APA) Hansen-Thomas, H., Langman, J., & Farias, T. (2018). The role of language objectives: Strengthening math and science teachers' language awareness with emergent bilinguals in secondary classrooms. LACLIL, 11(2), 193-214. DOI: 10.5294/laclil.2018.11.2.2 Received: 22/10/2018 Approved: 13/02/2019